Bridge Bible handbooks ; v. 1 : explaining the books of the Bible for the people of today's world - Fleming, Donald C. (Brisbane, QLD Bridgeway, 1988)
Contents : v. 1 : Genesis to Deuteronomy.
Brethren writer. Donated by the author.
Keywords: Bible -- introductions